THE IMPACT OF MERDEKA CURRICULUM CHANGES ON ARABIC LANGUAGE TEACHING QUALITY AT MADRASAH TSANAWIYAH - Yanti, Silvia Rahma; Amelia, Ulfi; Afifah, Shery Fara; Ma'ali, Abul; Rifana, Fitria (Edukasi: Jurnal Pendidikan, 2024)
This study aims to analyze the impact of changes introduced by the Merdeka Curriculum on the quality of Arabic language teaching at Madrasah Tsanawiyah. The research employs a qualitative approach with a case study method, collecting data through observations, and interviews with several Arabic language teachers at MTsN 1 Pasaman Barat as the research subjects. Data analysis is conducted using Creswell's method, involving procedures such as categorizing data, direct interpretation, pattern formation, and data analysis. The findings indicate both positive and negative impacts. On the positive side, teaching methods have become more interactive and participatory, leveraging technology and digital media to encourage students to learn independently and collaboratively. However, negative impacts include unequal access to technology, additional workload for teachers, and challenges in adapting to new evaluation methods. To ensure effective and equitable implementation, these obstacles need to be addressed by providing comprehensive technology training, administrative support to reduce teachers' workload, development of clear and practical evaluation guidelines.